2014
DOI: 10.1111/aor.12341
|View full text |Cite
|
Sign up to set email alerts
|

PEGylated Carboxyhemoglobin Bovine (SANGUINATE): Results of a Phase I Clinical Trial

Abstract: PEGylated carboxyhemoglobin bovine (SANGUINATE) is a dual action carbon monoxide releasing (CO)/oxygen (O2 ) transfer agent for the treatment of hypoxia. Its components inhibit vasoconstriction, decrease extravasation, limit reactive oxygen species production, enhance blood rheology, and deliver oxygen to the tissues. Animal models of cerebral ischemia, peripheral ischemia, and myocardial ischemia demonstrated SANGUINATE's efficacy in reducing myocardial infarct size, limiting necrosis from cerebral ischemia, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(50 citation statements)
references
References 13 publications
(6 reference statements)
0
50
0
Order By: Relevance
“…In a rat cerebral ischemia model (Klaus et al, 2010;Zhang et al, 2012), an even faster infusion rate (30 mL/h) and similar dose (10 mL/kg) resulted in only a minor rise in MAP. On the other hand, a clinical trial of healthy human volunteers (Misra et al, 2014) showed increases in MAP. Since we measured only blood pressures, other physiological changes besides volume expansion could play a role in the blood Table 2 Total Hb, PaO 2 , PaCO 2 and pH (mean ± SEM) in TBI rats.…”
Section: Discussionmentioning
confidence: 98%
“…In a rat cerebral ischemia model (Klaus et al, 2010;Zhang et al, 2012), an even faster infusion rate (30 mL/h) and similar dose (10 mL/kg) resulted in only a minor rise in MAP. On the other hand, a clinical trial of healthy human volunteers (Misra et al, 2014) showed increases in MAP. Since we measured only blood pressures, other physiological changes besides volume expansion could play a role in the blood Table 2 Total Hb, PaO 2 , PaCO 2 and pH (mean ± SEM) in TBI rats.…”
Section: Discussionmentioning
confidence: 98%
“…A phase I study has been completed and is consistent with the preclinical studies. SANGUINATE was found to be safe and well-tolerated in healthy human volunteers at doses of 80 mg/kg, 120 mg/kg, and 160 mg/kg [12]. Multiple doses of SANGUINATE have been used in Sickle Cell patients as well [13,14].…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacokinetic results found that SANGUINATE (160 mg/kg) had a prolonged T 1/2 in stable SCA patients (19.56 h) compared to that found in healthy volunteers (13.75 h) 7 . In the Phase I study with healthy volunteers, it was observed that haptoglobin levels were significantly reduced following SANGUINATE administration.…”
Section: Discussionmentioning
confidence: 95%
“…SANGUINATE is a novel construct of hemoglobin that contains carbon monoxide and pegylated bovine carboxyhemoglobin. It has been shown to reduce infarct volume in animal models7, 8 and has been administered under multiple emergency Investigational New Drugs (eINDs) 9, 10 11 and demonstrated the transfer of oxygen to hypoxic cells.…”
Section: Discussionmentioning
confidence: 99%